Taxation of Grants in the Russian Federation - A. E., Kanakova; D. Szpoper (Ekonomika Nauki)
The purpose of the article is to find out the peculiarities of grant taxation in Russia, depending on the subject composition of persons, implementing or attracted to the implementation of the grant. The article uses the following methods of scientific knowledge: analysis and synthesis, through which the provisions on grant taxation were first divided into constituent features and subsequently combined to formulate a position on the stated issue, also used the method of mental experiment, which allows to consider different options of taxation of persons involved in the implementation of grants. The result of this article was an indication of the absence or existence of an obligation to pay taxes on the grant for different entities: organizations and individuals as grant recipients and as entities involved in the implementation of the grant project. The decision to pay tax depends not only on which entity is the recipient of the grant, but also on which entity provides the grant. The existing approach to the solution of the considered question is characterized by complexity, biased differentiation criterion and requires correction.